2009
DOI: 10.1051/0004-6361/200912716
|View full text |Cite
|
Sign up to set email alerts
|

Relating basic properties of bright early-type dwarf galaxies to their location in Abell 901/902

Abstract: We present a study of the population of bright early-type dwarf galaxies in the multiple-cluster system Abell 901/902. We use data from the STAGES survey and COMBO-17 to investigate the relation between the color and structural properties of the dwarfs and their location in the cluster. The definition of the dwarf sample is based on the central surface brightness and includes galaxies in the luminosity range −16 ≥ M B > ∼ −19 mag. Using a fit to the color magnitude relation of the dwarfs, our sample is divided… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 93 publications
1
17
0
Order By: Relevance
“…Dressler & Gunn 1982;Poggianti et al 2004, but see Goto 2005Yan et al 2009 for an alternative view). In the Coma and Abell 2199 superclusters (z = 0.023), dwarf galaxies show a stronger relation between the SFR and local galaxy density than is found in the more massive galaxies (Haines et al 2006;Mahajan et al 2010a), while elsewhere (Barazza et al 2009) a strong colour-density relation is found in the Abell 901/902 system (z = 0.165). Clusters and rich groups at intermediate and high redshifts (z ∼ 0.5) have more luminous (M V ≤ −20) k+A galaxies, which seem to be missing in rich clusters at z ∼ 0 (Zabludoff et al 1996;Poggianti et al 2004;Nolan, Raychaudhury & Kabán 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Dressler & Gunn 1982;Poggianti et al 2004, but see Goto 2005Yan et al 2009 for an alternative view). In the Coma and Abell 2199 superclusters (z = 0.023), dwarf galaxies show a stronger relation between the SFR and local galaxy density than is found in the more massive galaxies (Haines et al 2006;Mahajan et al 2010a), while elsewhere (Barazza et al 2009) a strong colour-density relation is found in the Abell 901/902 system (z = 0.165). Clusters and rich groups at intermediate and high redshifts (z ∼ 0.5) have more luminous (M V ≤ −20) k+A galaxies, which seem to be missing in rich clusters at z ∼ 0 (Zabludoff et al 1996;Poggianti et al 2004;Nolan, Raychaudhury & Kabán 2007).…”
Section: Introductionmentioning
confidence: 94%
“…The luminosity-effective radius diagram presented by Barazza et al (2009) in Abell 901/902 (their fig. 2a) shows that their galaxies scatter about a mean constant effective radius.…”
Section: Surface Brightness-luminosity Relationmentioning
confidence: 99%
“…However, the origin of this large population of dEs is still a topic of ongoing debate, partly because they were found to follow a number of continuous relations in structure and colour with bright elliptical and/or lenticular galaxies (e.g. Côté et al 2007;Chen et al 2010;Kormendy & Bender 2012), but also since their identification Appendices are available in electronic form at http://www.aanda.org and detailed analysis are not yet possible at higher shifts (see Barazza et al 2009 for dEs in a z = 0.165 cluster). Clues to the origin of dEs may be given by the presence of weak disk features in a significant fraction of them (Jerjen et al 2000;De Rijcke et al 2003;Lisker et al 2006b), the presence of residual star formation activity in dEs outside of the densest environments (Lisker et al 2006a;Tully & Trentham 2008;Pak et al 2014) and the finding that these have significantly flatter shapes than dEs with low relative velocities in the Virgo cluster core ).…”
Section: Introductionmentioning
confidence: 99%